The Measurement of Social Value Impact of Ziswaf Using Social Return on Investment Model at Smart Ekselensia Indonesia - Achmad Ichsan Nusapati; Efri Syamsul Bahri; Ai Nur Bayinah (Faculty of Shariah and Law, UIN Syarif Hidayatullah Jakarta, 2020)
This study aims to measure the social value of the impact of Zakat, Charity/Shodaqoh, and Waqf (ZISWAF) produced by SMART Ekselensia Indonesia using Social Return on Investment (SROI). This study uses quantitative methods with a Social Return on Investment (SROI) measurement model. SROI measurement results show 32: 1. This can be interpreted that every IDR1 invested, it generates a social value of IDR32, which benefits are received by students and the community around SMART Ekselensia Indonesia. It also shows that SMART Ekselensia Indonesia has succeeded in creating social impacts that bring benefits to students and the surrounding community. The authenticity of this study is in the measurement of the impact of Zakat on mustahiq beneficiaries. A unique aspect of this study is the use of a social value measurement model of the impact of Zakat using the SROI approach.